Transport through hybrid superconducting/ferromagnetic double-path junction - Facio, T. J.S. [UNESP]; Orellana, P. A.; Jurelo, A. R.; Figueira, M. S.; Cabrera, G. G.; Siqueira, E. C. (Elsevier, 2017)
In this paper we study a double-path junction formed by a ferromagnetic and a superconductor lead. The first path connects the superconductor and ferromagnet directly while the second path connects these metals through a quantum dot. The whole system works as an Aharonov–Bohm interferometer allowing the study of the interference between these two paths under the presence of spin imbalance and Andreev bound states. We considered the effect of Fano interference on the electronic transmittance through the quantum dot and observed two regimes of conduction depending on the strength of the direct coupling. For the weak coupling regime, the transmittance presented the usual four resonances due to the Andreev bound states whereas for the strong coupling regime the profile was inverted and resonances became anti-resonances. However, even in the strong coupling regime it was possible to observe a central resonance due to the interference between the Andreev bound states. We have also studied the signatures of Fano interference on the average occupation within the quantum dot. The spin accumulation was analyzed and how it depends on the direct coupling and an external magnetic field applied to the system. The results obtained may be used in a possible experimental implementation of this system in order to probe spin related effects in ferromagnetic superconductor nanostructures.
Keywords: Aharonov–Bohm; Andreev transport; Ferromagnetism; Quantum dot; Superconductivity